Direct Composite Laminate Veneers: Three Case Reports - Bora Korkut; Funda Yanıkoğlu; Mahir Günda (Tabriz University of Medical Sciences, 2013)
Re-establishing a patient's lost dental esthetic appearance is one of the most important topics for contemporary dentistry. New treatment materials and methods have been coming on the scene, day by day, in order to achieve such an aim. Most dentists prefer more conservative and aesthetic approaches, such as direct and indirect laminate veneer restorations, instead of full-ceramic crowns for anteriors where aesthetics is really important. Laminate veneers are restorations which are envisioned to correct existing abnormalities, esthetic deficiencies and discolorations. Laminate veneer restorations may be processed in two different ways: direct or indirect. Direct laminate veneers have no need to be prepared in the laboratory and are based on the principle of application of a composite material directly to the prepared tooth surface in the dental clinic. Indirect laminate veneers may be produced from composite materials or ceramics, which are cemented to the tooth with an adhesive resin. In this case report, direct composite laminate veneer technique used for three patients with esthetic problems related to fractures, discolorations and an old prolapsed restoration, is described and six-month follow-ups are discussed. As a conclusion, direct laminate veneer restorations may be a treatment option for patients with the esthetic problems of anterior teeth in cases similar to those reported here.